Anti Leishmanial Activities of Some Anti-Depressant Drugs and Antifungal Drugs - Trivedi, Sagar S.; Lodhi, Geeta N.; Doifode, C. A.; Raut, Harsha (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Leishmanisis is wide range, worldwide, without drug, vaccine, secticide and has not sterileimmunity and efforts in this field have not been successful.Leishmaniasis is a complex vectorborne disease caused by different species of Leishmania. It affects at least 12 million people worldwide. Leishmaniasis is commonly associated with poor economic conditions and immunecompromised situations like HIV co infection. There is increasing in drug resistance tocommonly used therapeutics as well as lack of vaccine program. This leads to a perpetual searchfor a new drug for leishmaniasis. This review fundamentally deals with some antidepressantdrugs, and antifugal drugs showing the anti leishmanial activities. The antidepressant drugs are Imipramine, Sertraline, Ketanserin and Mianserin. Imipramine being a Tri Cyclic Antidepressant(TCA) drug kills Leishmania donovani elevating IL-12/IL-10 ratio. Sertraline belonging to theselective serotonin reuptake inhibitor (SSRI) drugs, removes parasite loads from spleen and liverprobably by declining cytoplasmic ATP consumption. Ketanserin is a serotonin receptor (5-HT2A/2C) antagonist that kills both amastigotes and promastigotes probably due to inhibition of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR). Mianserin belonging to the TCAgroup of drug, kills both promastigote and amastigote parasites also probably due to theinhibition of HMGR. The present review will give the summarized information about puttingsome old antidepressant drugs for the treatment of another disease like Leishmania. Manytopical antifungals have been available, two important antibiotics: amphotericin B to deal withsystemic mycosis and griseofulvin to supplement attack on dermatophtes . A number ofantifungal agents have been investigated in a rodent model for their parasiticidal activity againstvisceral leishmaniasis. These drugs have been administered intravenously both alone, and inconjunction with liposomes. All the compounds tested: griseofulvin, 5-fluorocytosine, andamphotericin B—together with the known antileishmanial drug pentamidine—displayedenhanced therapeutic activity when given in liposomal form. In the case of amphotericin,liposomes composed of hydrogenated lecithin, or containing cholesterol or ergosterol in themembrane, were least toxic to the mammalian host, and had the highest therapeutic capability.